Analisis Faktor Penyebab Terjadinya Sengketa Palm Kernel Expeller Yang Berulang Pada Tahun 2021-2023 - Deni Umar Dani; Sri Mulyani (CV. ITTC INDONESIA, 2024)
Year after year Tax Disputes are increasing, this is indicated by the increase in Tax Dispute Decisions on the website published by the Tax Court. This increase is not only due to the emergence of new problems, but also the problems that have occurred in the past. One of them is the Palm Kernel Expeller (PKE) dispute. In this case, research will be conducted to analyze the factors causing recurring value-added tax disputes through a case study of the Palm Kernel Expeller Dispute in 2021-2023. This research uses a Qualitative case study approach by using triangulation techniques in data collection. As for data analysis techniques, this study uses the Miles and Huberman Method by means of data reduction, data display, and conclusion drawing/verification. The results of this study indicate that there are differences in interpretation between taxpayers and tax authorities on Government Regulation No. 81 of 2015 and Minister of Finance Regulation No. 267 of 2015 related to exempted animal feed and animal feed ingredients that are not included in PMK 267 of 2015 so that they become taxable goods.